2021
DOI: 10.1029/2021gl092748
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of Arctic Sea‐Ice Loss and East Siberian Atmospheric Blocking to 2020 Record‐Breaking Meiyu‐Baiu Rainfall

Abstract: From mid-June to mid-July, a southward surge of cold air from high latitudes prevents the Asian summer monsoon from advancing further northward, generating a quasi-stationary west-east oriented front from central-east China to Japan (Ding, 1991;Tao & Chen, 1987;Zhu et al., 2003). The resultant persistent rainfall is referred to as the Meiyu in China, Changma in Korea, and Baiu in Japan. In June-July 2020, extremely heavy Meiyu-Baiu rainfall hits Japan and the middle-lower reaches of the Yangtze River in China,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…The S2S forecasting systems' features vary greatly among the models: dynamic framework, assimilation strategy, and more importantly, whether the systems directly assimilate sea ice concentration from the observations (e.g., the CMA versus the ECMWF and JMA). In particular, the Arctic Sea ice alters the mid-latitude variations and thus influences the 2020 record-breaking mei-yu (e.g., Chen et al 2021). Considering the great diversity in handling the sea ice, what impact it may have on the mei-yu forecast in some specific S2S models need further investigation in the future.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…The S2S forecasting systems' features vary greatly among the models: dynamic framework, assimilation strategy, and more importantly, whether the systems directly assimilate sea ice concentration from the observations (e.g., the CMA versus the ECMWF and JMA). In particular, the Arctic Sea ice alters the mid-latitude variations and thus influences the 2020 record-breaking mei-yu (e.g., Chen et al 2021). Considering the great diversity in handling the sea ice, what impact it may have on the mei-yu forecast in some specific S2S models need further investigation in the future.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…The precipitation events are controlled mainly by other factors, such as the onset/peak/withdrawal period of BCM front and typhoon activities. According to a recent study, the occurrence of blocking in high latitudes led to stopping the northward march of the BCM front, leading to record‐breaking BCM rainfall in June–July 2020 (Chen et al ., 2021). This suggests that further studies are needed to investigate the combined influence of the OKB and BCM front activities on precipitation over South Korea.…”
Section: Discussionmentioning
confidence: 99%
“…These studies found that the stable western Pacific subtropical high (WPSH) and strong Asian subtropical westerly jet (ASWJ) , Zhao et al 2022 were two factors that influenced directly the rainfall. The atmospheric circulation anomalies that contributed to the record-breaking rainfall in summer 2020 are believed to have been modulated by sea surface temperature anomalies in the Indian Ocean (Cai et al 2022, Zhou et al 2021 and tropical Pacific , Pan et al 2021, Chu et al 2022, the North Atlantic Oscillation (Liu et al 2020), active potential vorticity over the Tibetan Plateau (Ma et al 2022a), the Madden-Julian Oscillation (Liang et al 2021), and the Arctic seaice extent (Chen et al 2021). Obviously, the above research focused mainly on the impact of natural variability on record-breaking rainfall.…”
Section: Introductionmentioning
confidence: 99%